Relationship Between Ginsenoside Rg3 and Metabolic Syndrome - Lee, Hyunji; Kong, Gyeyeong; Tran, Quangdon; Kim, Chaeyeong; Park, Jisoo; Park, Jongsun (Frontiers in Pharmacology, 2020)
Metabolic syndrome is an important public health issue and is associated with a more affluent lifestyle. Many studies of metabolic syndrome have been reported, but its pathogenesis remains unclear and there is no effective treatment. The ability of natural compounds to ameliorate metabolic syndrome is currently under investigation. Unlike synthetic chemicals, such natural products have proven utility in various fields. Recently, ginsenoside extracted from ginseng and ginseng root are representative examples. For example, ginseng is used in dietary supplements and cosmetics. In addition, various studies have reported the effects of ginsenoside on metabolic syndromes such as obesity, diabetes, and hypertension. In this review, we describe the potential of ginsenoside Rg3, a component of ginseng, in the treatment of metabolic syndrome.